Collage Art Learning : Medium for Developing Creativity of Fourth Grade Students - Suci, Karisma Wulan; Gunandi, Gunandi (Jurnal Gentala Pendidikan Dasar, 2025)
This study analyzes collage art learning as a medium for developing creativity in 4th grade students at SDN Sambiroto 01 Semarang. Using descriptive qualitative approach with 30 students (12 boys, 18 girls), data were collected through participatory observation, semi-structured interviews with 5 students, and document analysis of 30 collage artworks. Research instruments adapted Torrance's five creativity aspects. Results show seed-based collage learning highly effective in developing creativity with high success rates: artwork planning (76.6%), color-based material selection (80%), neat technique implementation (76.6%), and patience demonstration (100%). Student creativity varied significantly with sensitivity aspect achieving highest score (3.6), followed by fluency and elaboration (3.4), flexibility and originality (3.2). Main challenges include limited material-tool variation, technical difficulties, and planning process variations. All students showed high satisfaction and continued interest. Seed-based collage learning proves effective as creativity development medium by providing extensive exploration space, developing fine motor skills, and facilitating meaningful learning aligned with Merdeka Curriculum principles.